Ancient recombination events and the origins of hepatitis E virus. Issue 1 (December 2016) - Kelly, Andrew; Netzler, Natalie; White, Peter
Abstract Background Hepatitis E virus (HEV) is an enteric, single-stranded, positive sense RNA virus and a significant etiological agent of hepatitis, causing sporadic infections and outbreaks globally. Tracing the evolutionary ancestry of HEV has proved difficult since its identification in 1992, it has been reclassified several times, and confusion remains surrounding its origins and ancestry. Results To reveal close protein relatives of theHepeviridae family, similarity searching of the GenBank database was carried out using a completeOrthohepevirus A, HEV genotype I (GI) ORF1 protein sequence and individual proteins. The closest non-Hepeviridae homologues to the HEV ORF1 encoded polyprotein were found to be those from the lepidopteran-infectingAlphatetraviridae family members. A consistent relationship to this was found using a phylogenetic approach; theHepeviridae RdRp clustered with those of theAlphatetraviridae andBenyviridae families. This puts theHepeviridae ORF1 region within the "Alpha-like" super-group of viruses. In marked contrast, the HEV GI capsid was found to be most closely related to the chicken astrovirus capsid, with phylogenetic trees clustering theHepeviridae capsid together with those from theAstroviridae family, and surprisingly within the "Picorna-like" supergroup. These results indicate an ancient recombination event has occurred at the junction of the non-structural and structure encoding regions, which led to the emergence of the entireHepeviridae family. TheAstroviridae capsid is also closely related to theTymoviridae family of monopartite, T = 3 icosahedral plant viruses, whilst its non-structural region is related to viruses of thePotyviridae ; a large family of plant-infecting viruses with a flexible filamentous rod-shaped virion. Thus, we identified a separate inter-viral family recombination event, again at the non-structural/structural junction, which likely led to the creation of theAstroviridae . Conclusions In summary, we have shown that new viral families have been created though recombination at the junction of the genome that encodes non-structural and structural proteins, and such recombination events are implicated in the genesis of important human pathogens; HEV, astrovirus and rubella virus.